Recent Progress on Transition-Metal-Mediated Reductive C(sp3)–O Bond Radical Addition and Coupling Reactions - Cheng, Li; Lin, Quan; Chen, Yunrong; Gong, Hegui (Synthesis, 2022)
In this short review, we summarize the recent developments on thermo-driven C(sp3)–O bond radical scission methods and their applications in the construction of C(sp3)–C bonds via conjugate addition with activated double bonds and reductive coupling mediated by economic 3d metals, in particular nickel. We have arranged the review based on three approaches for C(sp3)–O bond radical scission (vide infra). After generating the radical intermediates, their subsequent transformation into C(sp3)–C bonds enabled by C(sp3)–O cross-electrophile coupling with carbon electrophiles is discussed in detail.1 Introduction2 Direct Single-Electron Transfer to a C(sp3)–O Bond3 Radical Scission of Activated C(sp3)–O Bonds via Single-Electron Transfer to Protecting Groups4 In Situ Activation of Alcohols5 Summary and Outlook
Keywords: alcohols; C–O bonds; radicals; C–C bonds; reductive